Facial soft tissue thickness of the Japanese population determined using post mortem computed tomography images. (December 2020) - Tanaka, Chihiro; Utsuno, Hajime; Makino, Yohsuke; Minegishi, Saki; Ota, Jun; Iwase, Hirotaro; Sakurada, Koichi
Highlights: Bilateral mean facial soft tissue thickness of Japanese subjects was measured. The measurements from PMCTs are similar to that of living samples. The thickness data were not updated from 1948 until this report. The PMCT images were able to obtain accurate FSTT data. Abstract: Skull-photo superimposition (SPS) and forensic facial approximation (FFA) are techniques that help to determine facial soft tissue thickness in the Japanese population. The former is applied to existing samples from human skeletal remains, whereas the latter is applied as an estimation when a sample is not available. Both these forensic anthropological techniques are dependent on the mean value of facial soft tissue thickness (FSTT) with regard to ancestry, sex, and age. The positions of the orbits, ears, and nose are also used to estimate the FSTT. In Japan, some FSTT data have been reported. However, most of these data are based on the measurements of the midsagittal plane or were published before the 1950s. Initially, we aimed at establishing bilateral FSTT data (inclusive of the midsagittal plane) using 3D computed tomography (3DCT). However, the collection of 3DCT data involved the risk of radiation exposure. In Japan, some organizations obtained postmortem CT (PMCT) images prior to the autopsy of a deceased individual; therefore, we opted to collect, measure, and analyze these images instead of detecting the morphological differences in facial tissue. We updated the FSTT data of bilateral landmarks and compared the differences among three categories (sex, age, and body mass index). Even when the source of measurement was a cadaver, we obtained a measurement similar to that of living samples in the mid-to-upper face region. These findings are reported in this paper.